Implementation of Emergency Response System in Elementary School as an Effort to Increase Safety Culture from an Early Age - Evi Widowati; Rulita Hendriyani; Anik Setyo Wahyuningsih; Nurul Huda Agustiani; Roro Hapsari; Srinata Dwijaningtyas; Annisa Sari; Octavia Rahayu; Adelia Oktafiani; Tutik Lestari; Ani Suryani (Jurnal Penelitian Pendidikan, 2023)
Children are included in a vulnerable group that must be protected, both from the threat of natural disasters, non-natural disasters or social disasters. School is a place for children to spend a lot of time. Disaster events can occur anywhere and at any time, including at school and during school hours, so schools must have an adequate emergency response system to ensure the safety of all its citizens. The purpose of this study is to identify problems that exist in schools related to the implementation of the disaster response system and formulate indicators for the initiation of initial activities for implementing the emergency response system in elementary school. The research design uses a qualitative descriptive research. The results of identifying problems in Elementary School Y show that school has not implemented an emergency response and disaster mitigation system, but teachers' knowledge regarding multi-hazard mitigation is also still low. The conclusions obtained are that schools can apply initial activity initiation indicators for the implementation of an emergency response system including: preparation of an emergency response team complete with duties and roles, preparation of SOPs for emergency response at school, training and simulation of disaster mitigation, preparation of evacuation maps, installation of evacuation directions, determination gathering points, emergency response signs, installation of emergency response facilities at least Light Fire Extinguishers/APAR and instructions for their use, as well as developing a network of cooperation with related parties.